Compressive strength of concrete containing eggshell powder as partial cement replacement - Putra Jaya, Ramadhansyah; Mohd Arif, Sulaiman; Rokiah, Othman; Khairunisa, Muthusamy; Chong, Beng Wei; Chek, Y. C.; Youventharan, Duraisamy; Doh, Shu Ing (IOP Publishing Ltd, 2021)
The emission of carbon dioxide by cement manufacturing has caused a negative impact on society and environment such as the greenhouse effect. Disposal of eggshell has created a lot of environmental problems due to its reusability of material is low in many industries. Recent years, researchers have found the value of eggshell due to its high content of calcium carbonate. Consequently, it has encouraged the researchers to incorporate the eggshell as cement replacement for concrete production hence contributing to sustainable development of building materials. This experimental study is aimed to investigate the optimum percentage of eggshell as cement replacement for high strength concrete (HSC) and the effect on HSC were studied in terms of workability, compressive strength and rebound hammer test as well as ultrasonic pulse velocity (UPV). Four types of mix proportion of HSC were prepared namely 0% ESP, 5% ESP, 10% ESP and 15% ESP. Based on the experiment results, the workability of the fresh concrete mixtures decreases as the percentage of eggshell replacement increases. Mix containing 10% eggshell specimen achieved the highest compressive strength of 68.4 MPa at 28 days. Furthermore, the 10% eggshell specimen also achieved the highest value of rebound number of 42.1 and pulse velocity of 6.50km/s at 28 days. Correlation between actual compressive strength and UPV was more reliable and had accurate expression through regression analysis compared to rebound hammer test. Conclusively, the concrete containing 10% eggshell as partial cement replacement exhibits higher compressive strength than control concrete has the potential to be used as construction material.